Raman spectroscopy to assess the differentiation of bone marrow mesenchymal stem cells into a glial phenotype - Sulei Bautista-González; Nidia Jannette Carrillo González; Tania Campos-Ordoñez; Mónica Alessandra Acosta Elías; Martín Rafael Pedroza-Montero; Carlos Beas-Zárate; Graciela Gudiño-Cabrera (Regenerative Therapy, 2023)
Background: Mesenchymal stem cells (MSCs) are multipotent precursor cells with the ability to self-renew and differentiate into multiple cell linage, including the Schwann-like fate that promotes regeneration after lesion. Raman spectroscopy provides a precise characterization of the osteogenic, adipogenic, hepatogenic and myogenic differentiation of MSCs. However, the differentiation of bone marrow mesenchymal stem cells (BMSCs) towards a glial phenotype (Schwann-like cells) has not been characterized before using Raman spectroscopy. Method: We evaluated three conditions: 1) cell culture from rat bone marrow undifferentiated (uBMSCs), and two conditions of differentiation; 2) cells exposed to olfactory ensheathing cells-conditioned medium (dBMSCs) and 3) cells obtained from olfactory bulb (OECs). uBMSCs phenotyping was confirmed by morphology, immunocytochemistry and flow cytometry using antibodies of cell surface: CD90 and CD73. Glial phenotype of dBMSCs and OECs were verified by morphology and immunocytochemistry using markers of Schwann-like cells and OECs such as GFAP, p75 NTR and O4. Then, the Principal Component Analysis (PCA) of Raman spectroscopy was performed to discriminate components from the high wavenumber region between undifferentiated and glial-differentiated cells. Raman bands at the fingerprint region also were used to analyze the differentiation between conditions. Results: Differences between Raman spectra from uBMSC and glial phenotype groups were noted at multiple Raman shift values. A significant decrease in the concentration of all major cellular components, including nucleic acids, proteins, and lipids were found in the glial phenotype groups. PCA analysis confirmed that the highest spectral variations between groups came from the high wavenumber region observed in undifferentiated cells and contributed with the discrimination between glial phenotype groups. Conclusion: These findings support the use of Raman spectroscopy for the characterization of uBMSCs and its differentiation in the glial phenotype.